Multicentre prospective observational study on professional wound care using honey (Medihoney™). Issue 3 (11th April 2012) - Biglari, Bahram; Moghaddam, Arash; Santos, Kai; Blaser, Gisela; Büchler, Axel; Jansen, Gisela; Längler, Alfred; Graf, Norbert; Weiler, Ursula; Licht, Verena; Strölin, Anke; Keck, Brigitta; et al.
<x xml:space="preserve">Abstract</x> In recent years, the treatment of wounds with honey has received an increasing amount of attention from healthcare professionals in Germany and Austria. We conducted a prospective observational multicentre study using Medihoney™ dressings in 10 hospitals – nine in Germany and one in Austria. Wound‐associated parameters were monitored systematically at least three times in all patients. Data derived from the treatment of 121 wounds of various aetiologies over a period of 2 years were analysed. Almost half of the patients were younger than 18 years old, and 32% of the study population was oncology patients. Overall, wound size decreased significantly during the study period and many wounds healed after relatively short time periods. Similarly, perceived pain levels decreased significantly, and the wounds showed noticeably less slough/necrosis. In general, our findings show honey to be an effective and feasible treatment option for professional wound care. In addition, our study showed a relationship between pain and slough/necrosis at the time of recruitment and during wound healing. Future comparative trials are still needed to evaluate the extent to which the positive observations made in this and other studies can definitely be attributed to the effects of honey in wound care.